-10(s+5)=-33

Simple and best practice solution for -10(s+5)=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(s+5)=-33 equation:


Simplifying
-10(s + 5) = -33

Reorder the terms:
-10(5 + s) = -33
(5 * -10 + s * -10) = -33
(-50 + -10s) = -33

Solving
-50 + -10s = -33

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '50' to each side of the equation.
-50 + 50 + -10s = -33 + 50

Combine like terms: -50 + 50 = 0
0 + -10s = -33 + 50
-10s = -33 + 50

Combine like terms: -33 + 50 = 17
-10s = 17

Divide each side by '-10'.
s = -1.7

Simplifying
s = -1.7

See similar equations:

| 4(m-7)=5(m+8) | | 3e^2+20e-7= | | 4p+5q=33 | | 4a-2a/5=18 | | 18x1/3 | | 3x^2-3x-4x-6=0 | | 3D+D+4d-8d= | | y*1/8=128 | | 21/3x18 | | 5y+8=2y-10 | | 24/x-3=3 | | (7x+7)5y=140 | | 7x+10=3x-22 | | 7x+7(5y)=140 | | 12-6(2x-3)= | | 2(3s+9)=63 | | 3(3s+5)=60 | | 3(4x-2)=x+16 | | 4x-35=3(5x+3) | | 4log(2x-1)=0 | | (u-5)*8=16 | | 4(2l+5)=100 | | 4(3s+7)=172 | | 6(l+6)=168 | | (e+2)*6=42 | | C=60t+800 | | (f/6)-4=1 | | (q-3)*6=12 | | 150/144 | | (2x+1)/4=2 | | 21=63 | | sin(21)=cos(5x+9) |

Equations solver categories